2020
DOI: 10.14738/abr.83.8018
|View full text |Cite
|
Sign up to set email alerts
|

21st Century Challenges Confronting Women Entrepreneurs in Southwest Nigeria

Abstract: Women Entrepreneurs play a significant role in the global economy in this 21 st Century. The purpose of this study is to examine the specific challenges faced by women entrepreneurs in the southwestern states of Nigeria. Data were collected from businesses owned by women who reside within the six state capitals of Southwestern states of Nigeria. The cities are Lagos, Abeokuta, Ibadan, Oshogbo, Akure, and Ado-Ekiti. Similar big cities within each state were surveyed to increase the number of respondents for sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The outcome of the investigation appears that the awareness and information about Sustainable Development Goals (SDGs) 2030 components, particularly goal five (5), is weak amongst female-owned businesses in Kenya and Nigeria. The study findings confirmed the results of other studies noted in the literature review that a significant portion of women is more exclusively inhibited than their male counterparts due to gender inequality (Aladejebi, 2020;Balakrishnan & Low, 2016;Sarkis, 2019;Ukwueze,2022). Many of the respondents in Kenya and Nigeria women seem to have difficulty growing their businesses due to gender bias, lack of raising capital, and inadequate technical and managerial skills; having access to training would provide information such as the fundamental skills and experiences needed to launch the businesses.…”
Section: Conclusion and Recommendationssupporting
confidence: 90%
“…The outcome of the investigation appears that the awareness and information about Sustainable Development Goals (SDGs) 2030 components, particularly goal five (5), is weak amongst female-owned businesses in Kenya and Nigeria. The study findings confirmed the results of other studies noted in the literature review that a significant portion of women is more exclusively inhibited than their male counterparts due to gender inequality (Aladejebi, 2020;Balakrishnan & Low, 2016;Sarkis, 2019;Ukwueze,2022). Many of the respondents in Kenya and Nigeria women seem to have difficulty growing their businesses due to gender bias, lack of raising capital, and inadequate technical and managerial skills; having access to training would provide information such as the fundamental skills and experiences needed to launch the businesses.…”
Section: Conclusion and Recommendationssupporting
confidence: 90%
“…Therefore, banking institutions and other consulting experts need to change their attitudes and offer help to female entrepreneurs. Most institutions don't offer assistance to female-driven enterprises as they don't consider them to have positive contributions to economic development (Aladejebi, 2020).…”
Section: Access To Finance and Entrepreneurshipmentioning
confidence: 99%
“…Therefore, a liberal feminist view allows us to explore and resolve the challenges faced by women in integrating digital economic activities. Removal of challenges to women's integration in digital economic activities would enable them to function better in business activities and accelerate their business and personal growth (Shoma, 2019; Aladejebi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liberal feminism is one of the significant theoretical bases, which argues that women's status in society is based on unequal opportunities and segregation from men (Aladejebi, 2020; Wolff, 2007). According to liberal feminist theory, gender differences advantage men over women.…”
Section: Literature Reviewmentioning
confidence: 99%